2018
DOI: 10.3390/met8080600
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Performance of a Three-Layered Al/7075–B4C/Al Composite Prepared by Semi Continuous Casting and Hot Rolling

Abstract: A three-layered composite material, consisting of an Al outer layer and a 7075-10 wt % B4C inner layer, was fabricated by semi-continuous casting and following a hot rolling process. The composite exhibits a clear layered structure with a good interfacial bond between layers. In the sessile drop experiment, the Al alloy melt dropped on the 7075-B4C composite at 650 °C, with the contact angle decreasing from 105° to 25° in 50 s, indicating that the infiltration and spreading both played important roles in the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The interface between the different layers is clear and visible from a macro perspective of the Al-B 4 C/Al laminated composites section shown in Figure 2 (based on the distinct darkness difference between 6061Al and 15 vol.% B 4 C/6061Al). However, the interface between the B 4 C/Al layer and Al layer is not integrated nor continuous from a micro perspective in Figure 5b, which exhibits an alternative arrangement of the B 4 C particles and Al matrix [23,27,31]. The interface morphology is different from the same straight and continuous interfaces of the metal laminated composites [1,9,11,14].…”
Section: Interfacial Microstructure Of Al-b 4 C/al Laminated Compositesmentioning
confidence: 95%
See 1 more Smart Citation
“…The interface between the different layers is clear and visible from a macro perspective of the Al-B 4 C/Al laminated composites section shown in Figure 2 (based on the distinct darkness difference between 6061Al and 15 vol.% B 4 C/6061Al). However, the interface between the B 4 C/Al layer and Al layer is not integrated nor continuous from a micro perspective in Figure 5b, which exhibits an alternative arrangement of the B 4 C particles and Al matrix [23,27,31]. The interface morphology is different from the same straight and continuous interfaces of the metal laminated composites [1,9,11,14].…”
Section: Interfacial Microstructure Of Al-b 4 C/al Laminated Compositesmentioning
confidence: 95%
“…Chao et al studied the ballistic performance of B 4 C/AA2024 functionally graded composites with wide range B 4 C volume fraction, and found that crack deflection appears in the interface of the top and middle layer [20]. A three-layered Al/7075-B 4 C/Al composite was prepared by semi continuous casting and hot rolling, significantly reducing the bullet speed during the projectile impact test [27]. It is necessary to do the basic research on the properties and mechanism of laminated PRMMCs under different loading to support more application research.…”
Section: Introductionmentioning
confidence: 99%
“…e metal-cermet three-layered composite combines the advantages of both metal matrix composites and the three-layered composite materials [5,6]. It is an ideal material in the areas of light protection and bulletproof armor for which ballistic performance is an important index.…”
Section: Introductionmentioning
confidence: 99%